CHALLENGES AND ADVANCES IN CATTLE REPRODUCTIVE MANAGEMENT (International Seven Journal of Multidisciplinary, 2026)
Bovine reproduction is a fundamental pillar for the economic and productive viability of livestock farming; however, it faces challenges in fertility and genetic improvement due to low heritability in selection programs focused primarily on productivity. This results in undesirable genetic imbalances, directly impacting reproductive efficiency and animal welfare. This study aimed to review and analyze recent advances in the field, emphasizing the integration of genomics, physiology, and management. The methodology consisted of a literature review of articles published between 2020 and 2025 in the PubMed database. The analyzed studies demonstrate that, despite the low heritability of reproductive traits, consistent gains can be achieved through more refined and integrated selective strategies, especially with the identification of selection signatures associated with fertility, environmental adaptation, and productive longevity. Furthermore, the study highlights the relevance of including male fertility assessment and the use of digital monitoring technologies to support reproductive management. The results indicate that the application of genomic tools, combined with reproductive assessment and appropriate management, contributes to improving reproductive efficiency and the sustainability of bovine reproduction systems in modern animal production systems.